FORMATION OF PALLADIUM(II) HYDROXYCHLORIDE COMPLEXES AND PRECIPITATES IN SODIUM CHLORIDE SOLUTIONS AND SEAWATER - Byrne R.H.; Yao W. (My University, 2000)
Spectrophotometric measurements of Pd(II) in 0.5 M NaCl indicate that the PdCl3OH2- formation constant at 25°C is ClK*1 = [PdCl3OH2-][H+][Cl-][PdCl42-]-1 = 10-8.98. This constant is more than two orders of magnitude smaller than previous results derived through solubility analysis. Kinetic experiments indicate that equilibration between PdCl42- and PdCl3OH2- is complete in less than one second. The discrepancy between depictions of Pd(II) speciation obtained by using spectrophotometric and solubility analysis is apparently caused by the formation of mixed hydroxychloride solid phases (PdClaOH2-a), rather than pure Pd(OH)2(s), when Pd(OH)2(s) is equilibrated in concentrated chloride solutions at high pH. In Pd(II) solubility analysis, and solubility analyses of other strongly hydrolyzed metals in seawater, the composition of the solid phase must be carefully examined for appropriate deconvolution of data.